Uma abordagem lúdica de conceitos de cinemática e dinâmica newtoniana com alunos do 9° ano do ensino fundamental - Silva, Samara de Medeiros (2017)
The specific training of science teachers in the ninth grade of primary education has been discussed in the scientific community of education area for a few decades. The national education plan has as one of its goals the training of teachers in specific graduate curses for each area. However in most of schools in the interior cities it’s observed that professionals from other areas are tasked to teach concepts for which they don’t have domain. In this dissertation work, it was discussed the school realities of the primary education of the Seridó region of Rio Grande do Norte. The used methodology was developed at Escola Municipal Francisco Quinino de Medeiros, located in Ipueira-RN, in a class of ninth grade of elementary school. The proposed educational product is applied as an alternative to the teaching science in a playful way, at the same time interactive and dynamic on how to approach the concepts of Newtonian kinematic and dynamics with ninth grade students of the elementary school, avoiding the use of the traditional method. Methodologically, the research used the following instrument: the questionnaire in function, especially the number of involved in the research. By analyzing the teachers and students, in order to address the main areas of research. The questionnaire is an instrument that, simple and efficient way, serves well to this demand. As a way of learning evaluation of the students was considered qualitative aspects, such as student participation during the process of development, activities and quantitative aspects, through the data obtained in the initial questionnaire pre-test, post-test and final. The results show that there has been a change of Newtonian conceptions on the part of students. The Newtonian concepts were addressed through the use of low-cost experiments, use of learning objects and non-formal environments of learning